Population structure and dynamics of Campylobacter populations carried by wild birds and chickens reared in a free-range woodland environment - Colles, F; Colles, Frances M (2006)
﻿ Ingestion of contaminated chicken meat is a major cause of Campylobacteriosis in Europe and the USA. The environment, including wild birds, is considered to be an important reservoir for chicken colonization. The aims of this study were to determine the population structure of Campylobacter amongst chicken and wild bird sources on a single farm, and to establish the extent to which genotypes flow between them and ultimately infect humans, using MLST and antigen sequence typing. A pilot study amongst farm animals and wild birds in Lancashire demonstrated that Campylobacter genotypes from human disease were common on the farm and could be isolated from more than one animal source. Between 30-50% of wild geese and Starlings were shedding Campylobacter, with a seasonal peak in shedding rate in Spring. Genotypes were divergent from those previously isolated from human disease, retail meat and farm animal sources, with the majority being restricted to the host source. The carriage rate of Campylobacter was between 70- 100% amongst 78 free-range poultry flocks tested at 56 days of age. Up to seven genotypes were found to co-exist within a flock, and genotypes varied throughout the year on a random basis. Some Campylobacter strains were isolated from one farm site only, but a small percentage of them had spread nationally and were stable over a period of a decade. A total of 23% of Campylobacter isolates from free-range chickens were indistinguishable to those from human disease, and 5% were indistinguishable from wild birds. A total of 6% of genotypes isolated from wild birds were indistinguishable from those isolated from human disease. Wild birds could not be completely disregarded as a potential reservoir of Campylobacter for both humans and poultry, but their role is likely to be limited.